Body-mass index and all-1 cause mortality: Individual-participant-data meta-analysis of 239 prospective studies in four continents - Di Angelantonio, E; Woodward, M; Cairns, B; Lewington, S; Collins, R; Green, J; Halsey, J; Reeves, G; Yang, L; Beral, V; Chen, Z; Peto, R (Elsevier, 2016)
Background: Overweight and obesity are increasing worldwide. To help assess their relevance to mortality in different populations we conducted individual-participant-data meta-analyses of the prospective studies of body mass index (BMI), limiting confounding and reverse causality by restricting analyses to never-smokers and excluding prior disease and the first 5 years of follow- up. Methods: Of 10,625,411 participants in Asia, Australia/New Zealand, Europe, and North America from 239 prospective studies (median follow-up 13·7 [IQR: 11·4-14·7] years), 3,951,455 in 189 studies were never-smokers without specific chronic diseases at recruitment who survived 5 years, of whom 385,879 died. The primary analyses are of these deaths, using age and sex-adjusted hazard ratios (HRs). Findings: All-cause mortality was minimal (HR=1) at BMI (kg/m2) 20-25, and increased significantly both just below this range (BMI 18·5-<20: HR=1·13, 95%CI 1·09-1·17; BMI 15- <18·5: HR=1·51, 1·43-1·59) and throughout the overweight range just above it (BMI 25-<27·5: HR=1·07, 1·07-1·08; BMI 27·5-<30: HR=1·20, 1·18-1·22). Continuing upwards, HRs for obesity grade I, II, and III (BMI 30-<35, 35-<40, 40-<60) were 1·45 (1·41-1·48), 1·94 (1·87-2.01), and 2·76 (2·60-2·92), respectively. For BMI>25, mortality increased approximately log-linearly with BMI; HR per 5 units higher BMI was 1·31 (1·29-1·33) in all regions; 1·39 (1·35-1·43) in Europe; 1·29 (1·26-1·32) in North America, 1·39 (1·34-1·44) in East Asia, and 1.31 (1.27, 1.35) in Australia/New Zealand. This HR per 5 units higher BMI (for BMI>25) was greater in younger than older people (1.52 at 35–49 years vs 1·21 at 70-89 years; Pheterogeneity<0·0001), greater in men than women (1·51 vs 1·30; Pheterogeneity<0·0001), but similar in studies with self-reported and measured BMI. Interpretation: The associations of both overweight and obesity with higher all-cause mortality were broadly consistent in four continents. This supports strategies to combat the entire spectrum of excess adiposity in many populations.